Immigration History and Whiteness Studies: American and Australian Approaches Compared - Shiells, Georgia (History compass, 2010)
The emergence of whiteness studies as a discrete field of academic enquiry has had important implications across a range of fields, including history. In particular, insights drawn from whiteness studies can be fruitfully applied to the study of immigration history. American scholars have shown that, in their country, whiteness was a crucial marker used in order to exclude certain immigrant groups and the white status of immigrants was tenuous and conditional. In Australia, historians across a range of fields have embraced whiteness studies. And yet, historical studies of the shifting racial status of continental European immigrants - particularly those from Southern and Eastern Europe, whose whiteness was most frequently questioned - have been fewer in number and less extensive than American studies. This article considers that North American and Australian scholarly work which examines the role of whiteness in the historical experience of continental European immigrants during the late 19th and early 20th centuries. It suggests that whiteness studies can offer Australian immigration history a useful frame for historical analysis; however, Australian work will inevitably reflect different preoccupations to that of American scholars, and some caution should be exercised in importing American approaches wholesale.